Studies on Acetyl-Coenzyme A Synthetase of Yeast: Inhibition by Long-Chain Acyl-Coenzyme A Esters - Satyanarayana, T. (1973)
Long-chain acyl-coenzyme A (CoA) compounds (palmityl, stearyl, and oleyl) were found to be potent inhibitors of acetyl-CoA synthetase (ACS) of Saccharomyces cerevisiae strain LK2G12 from aerobic, but not from nonaerobic, cells. The effectiveness of the inhibitors of the aerobic enzyme was in the following order: palmityl-CoA < stearyl-CoA < oleyl-CoA. Short-chain acyl-CoA compounds (propionyl, butyryl, and valeryl) and long-chain fatty acids had no effect on ACS from either source. The inhibition by oleyl-CoA was found to be dependent on enzyme concentration, whereas the inhibition by palmityl- and stearyl-CoA was independent of ACS concentration. Inhibition by palmityl-CoA was noncompetitive with respect to both acetate and CoA, and with increasing concentration of inhibitor the pattern was sigmoidal, with a Hill value of 3.24. At maximally inhibitory concentrations of palmityl-CoA, a small amount of enzyme activity remained. This noninhibitable enzyme in aerobic cells was shown not to be of nonaerobic origin.